1990
DOI: 10.1111/j.1365-2125.1990.tb03654.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multiple dosage on the kinetics of glucuronidation and sulphation of diflunisal in man.

Abstract: 1 The single (250 and 500 mg) and multiple dose (250 and 500 mg twice daily for 15 days) pharmacokinetics of diflunisal were compared in young volunteers. 2 The plasma clearance of diflunisal was lowered significantly after multiple dose administration (5.2 ± 1.2 and 4.2 ± 0.7 ml min-' for the 250 and 500 mg twice daily regimens, respectively) as compared with single dose administration (11.4 ± 3.1 and 9.9 + 2.0 ml min-' for the 250 and 500 mg single doses, respectively).3 The partial metabolic clearances of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The ratios of AUC of anthraquinone S to those of correspondent G/S following seven-dose administration were compared with those following single dose (Shia et al, 2009) and indicated that the ratios of S of aloe-emodin, rhein and emodin after sevendose administration of RP were increased by 744%, 144% and 460%. This phenomenon may stem from the saturated glucuronidation following multiple-dose administration like diflunisal (Verbeeck et al, 1990).…”
Section: Discussionmentioning
confidence: 97%
“…The ratios of AUC of anthraquinone S to those of correspondent G/S following seven-dose administration were compared with those following single dose (Shia et al, 2009) and indicated that the ratios of S of aloe-emodin, rhein and emodin after sevendose administration of RP were increased by 744%, 144% and 460%. This phenomenon may stem from the saturated glucuronidation following multiple-dose administration like diflunisal (Verbeeck et al, 1990).…”
Section: Discussionmentioning
confidence: 97%
“…Although biliary excretion of the diflunisal glucuronides was demonstrated in cholecystectomised patients with T-tube drainage, the results of that study indicate that it probably only contributes minimally to the overall elimination of the glucuronide conjugates in subjects with normal kidney function [34]. Diflunisal is highly bound to albumin in human plasma [35] and shows saturation of binding sites at plasma concentrations obtained following chronic administration of therapeutic doses of the drug [24].…”
Section: Discussionmentioning
confidence: 87%
“…Equilibrium dialysis was carried out as previously described [23,24]. For the in vitro experiments, plasma obtained from four healthy volunteers was pooled.…”
Section: Plasma Protein Bindingmentioning
confidence: 99%
See 2 more Smart Citations